The Effect of Balanced Nutrition Education on Mothers’ Perceptions, Intentions, and Knowledge Regarding the Use of Complementary Feeding Broth Powder Made from Grouper Fish Scale Waste - La Ode Sahlan Zulfadlih; Indri Setyawati; Anisa Purnamasari (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Nutritional problems among children under five in coastal areas remain relatively high, partly due to limited access to animal-based protein sources. On the other hand, the potential of marine resources has not been optimally utilized, including grouper fish scales (Epinephelus sp.), which are rich in protein, calcium, and collagen. The innovation of processing these wastes into complementary feeding (MP-ASI) stock powder holds potential as both a nutritional solution and an environmental management strategy. This study aims to analyze the effect of balanced nutrition education on mothers’ knowledge, perceptions, and intentions regarding the use of grouper fish-scale-based MP-ASI stock powder. Objectives: This study aimed to analyze the effect of balanced nutrition education on mothers’ knowledge, perceptions, and intentions regarding the use of grouper fish-scale-based MP-ASI stock powder. Methods: This research employed a pre-experimental design with a one-group pre-test–post-test approach involving 30 mothers with children aged 6–24 months in Mekar Jaya Village, Konawe Regency, Southeast Sulawesi. A structured questionnaire was used to measure knowledge, perception, and intention, with prior validity and reliability testing (Cronbach’s alpha ≥0.70). Data were analyzed using the Shapiro-Wilk normality test, Levene’s homogeneity test, paired t-test, Wilcoxon signed-rank test, and Pearson correlation test. Results: The findings demonstrated a significant improvement in knowledge (p<0.001), perception (p<0.001), and intention (p<0.001) after the educational intervention. Correlation analysis revealed positive associations between knowledge and perception (r=0.52; p=0.004), knowledge and intention (r=0.47; p=0.009), and perception and intention (r=0.61; p<0.001). Conclusions: Balanced nutrition education is effective in enhancing knowledge, fostering positive perceptions, and encouraging mothers’ intention to use grouper fish-scale-based MP-ASI stock powder. This study is relevant as a foundation for developing nutrition education strategies and food innovations based on local potential to support the improvement of child nutrition in coastal areas.